Didactic - methodological reflections for the preparation of intermediate level educators in references to the stimulation of the thought in the preschool age - Mercedes Eligia Martínez Pérez (Revista MENDIVE, 2014)
This article is an approach to preschool special ty in upper secondary teacher training; it is given, concerning the development of thinking in preschool, considerations about its stimulation from t he use of didactic methodological procedures; intellectual skills that best work in these ages are specified; their actions and operations and indicators are suggested to evaluate this pro cess.